Developing a platform system for gene delivery: amplifying virus-like particles (AVLP) as an influenza vaccine. (December 2017) - Wei, Huiling; Chen, Zhenhai; Elson, Andrew; Li, Zhuo; Abraham, Mathew; Phan, Shannon; Kristhnamurthy, Sateesh; McCray, Paul; Andrews, Seth; Stice, Steve; Sakamoto, Kaori; Jones, Cheryl; et al.
Abstract Delivery of a gene of interest to target cells is highly desirable for translational medicine, such as gene therapy, regenerative medicine, vaccine development, and studies of gene function. Parainfluenza virus 5 (PIV5), a paramyxovirus with a negative-sense RNA genome, normally infects cells without causing obvious cytopathic effect, and it can infect many cell types. To exploit these features of PIV5, we established a system generating self-amplifying, virus-like particles (AVLP). Using enhanced green fluorescent protein (EGFP) as a reporter, AVLP encoding EGFP (AVLP–EGFP) successfully delivered and expressed the EGFP gene in primary human cells, including stem cells, airway epithelial cells, monocytes, and T cells. To demonstrate the application of this system for vaccine development, we generated AVLPs to express the HA and M1 antigens from the influenza A virus strain H5N1 (AVLP–H5 and AVLP–M1H5). Immunization of mice with AVLP–H5 and AVLP–M1H5 generated robust antibody and cellular immune responses. Vaccination with a single dose of AVLP–H5 and M1H5 completely protected mice against lethal H5N1 challenge, suggesting that the AVLP-based system is a promising platform for delivery of desirable genes. Virotherapy: using virus-like particles as a 'trojan horse' An 'imitation virus' can be used to deliver genetic material to target cells, with farreaching potential for medical application. The capacity to safely and affordably introduce genes into cells is highly-sought. A team led by the University of Georgia's Biao He created a protein shell using parainfluenza virus 5 proteins, with the resultant particles possessing the ability to infect multiple types of cell and deliver desired genetic material. The team proved the utility of their system by using it to express immunity-promoting components of avian influenza virus in live mice—successfully vaccinating the animals, and enabling them to survive a subsequent lethal infection. His group also showed that their system is also able to deliver and express genes in human cells, prompting further research into this useful tool.